Zwitterionic polymer ligands: an ideal surface coating to totally suppress protein-nanoparticle corona formation?. (October 2019) - Debayle, Manon; Balloul, Elie; Dembele, Fatimata; Xu, Xiangzhen; Hanafi, Mohamed; Ribot, Francois; Monzel, Cornelia; Coppey, Mathieu; Fragola, Alexandra; Dahan, Maxime; Pons, Thomas; Lequeux, Nicolas
Abstract: In the last few years, zwitterionic polymers have been developed as antifouling surface coatings. However, their ability to completely suppress protein adsorption at the surface of nanoparticles in complex biological media remains undemonstrated. Here we investigate the formation of hard (irreversible) and soft (reversible) protein corona around model nanoparticles (NPs) coated with sulfobetaine (SB), phosphorylcholine (PC) and carboxybetaine (CB) polymer ligands in model albumin solutions and in whole serum. We show for the first time a complete absence of protein corona around SB-coated NPs, while PC- and CB-coated NPs undergo reversible adsorption or partial aggregation. These dramatic differences cannot be described by naïve hard/soft acid/base electrostatic interactions. Single NP tracking in the cytoplasm of live cells corroborate these in vitro observations. Finally, while modification of SB polymers with additional charged groups lead to consequent protein adsorption, addition of small neutral targeting moieties preserves antifouling and enable efficient intracellular targeting.